Welding wire, laser welded structural part, preparation method thereof, and vehicle

By using welding wire with specific chemical components for laser welding, the problems of insufficient toughness of welds of high-strength grade materials and delayed cracking caused by hydrogen are solved, and high-strength and toughness are realized. The laser welding structural parts are suitable for welding of high-strength steels. , meets the needs of high security and lightweight.

CN118808987BActive Publication Date: 2024-12-17XIAOMI EV TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411296024.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2024-12-17
Estimated Expiration
2044-09-14

AI Technical Summary

Technical Problem

The laser weld welds of high-strength grade materials in the prior art are insufficient in toughness, and there is a risk of delayed cracking due to hydrogen.

Method used

Welding wires containing specific chemical components, such as 0.26~0.48% C, 0.1~0.3% Si, 0.8~3% Mn, 0.1~0.4% Cr, 0.03~0.1% Zr, and optional Ti, The Nb and Co welding wires are welded by laser wire fill welding and hot stamping to form high-strength and tough laser welded structural parts.

Benefits of technology

It improves the strength and toughness of the weld, reduces the risk of delayed cracking caused by hydrogen, and realizes high-strength, high safety and lightweight vehicle structural parts, suitable for high-quality laser welding of high-strength steel.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118808987B_ABST
    Figure CN118808987B_ABST
Patent Text Reader

Abstract

The present disclosure relates to a welding wire, a laser-welded structural part, a preparation method thereof and a vehicle. Based on the total weight of the welding wire, the welding wire contains 0.26-0.48 wt% C, 0.1-0.3 wt% Si, 0.8-3 wt% Mn, 0.1-0.4 wt% Cr, 0.03-0.1 wt% Zr, and the remainder is Fe and unavoidable impurity elements. The welding wire provided by the present disclosure can realize high-quality laser welding of high-strength grade steel, with high weld strength, good toughness, strong resistance to hydrogen-induced delayed cracking, strong versatility and low cost, and is suitable for the production of high-strength, high-safety and lightweight vehicle structural parts and other key industrial components.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a welding wire, a laser-welded structural component, a preparation method thereof, and a vehicle. Background Art

[0002] In recent years, with the urgent need for energy conservation and environmental protection and the improvement of safety requirements, lightweight and safety have become the common pursuit of the automotive manufacturing industry, and high-strength steel has received more and more attention in the field. In automobile manufacturing, the laser welding method can weld together steel plates of different thicknesses, different materials and even different surface conditions. This method can place the required materials in the required position of the parts, thereby achieving the optimal cost, weight and safety performance. Hot stamping of laser-welded sheets can reduce the number of body parts while reducing weight, improve manufacturing accuracy and make the parts have better collision performance, and the lightweight effect is more obvious.

[0003] In order to meet more stringent collision requirements and achieve maximum lightweight, various welded parts have come into being. Welded parts can be welded not only from materials with the same strength and thickness (such as steel plates), but also from a combination of materials with different strengths (strength levels, for example, include: tensile strength of 500MPa, 1000MPa, 1500MPa, 2000MPa, etc.) and thicknesses. However, in the prior art, when laser welding high-strength materials to form welded parts, in order to obtain high-strength welds, welding wires with high carbon and high manganese are often used, but the resulting welds often have insufficient toughness and are at greater risk of hydrogen-induced delayed cracking. Summary of the invention

[0004] The purpose of the present disclosure is to provide a welding wire, a laser-welded structural part, a method for preparing the same, and a vehicle, so as to enhance the strength and toughness of the weld and improve its resistance to hydrogen-induced delayed cracking.

[0005] In order to achieve the above-mentioned objectives, the first aspect of the present disclosure provides a welding wire, which contains, based on the total weight of the welding wire, 0.26~0.48 weight % of C, 0.1~0.3 weight % of Si, 0.8~3 weight % of Mn, 0.1~0.4 weight % of Cr, 0.03~0.1 weight % of Zr, and the remainder is Fe and unavoidable impurity elements.

[0006] Optionally, the welding wire further contains Ti, Nb and Co; based on the total weight of the welding wire, the welding wire contains 0.01-0.08 wt % Ti, 0.01-0.06 wt % Nb and 0.01-0.1 wt % Co.

[0007] Optionally, based on the total weight of the welding wire, the total content of Ti element and Nb element is 0.02-0.1 wt %.

[0008] Optionally, in the welding wire, the weight ratio of Zr element to Ti element is not less than 2.5.

[0009] Optionally, based on the total weight of the welding wire, the welding wire contains 0.3~0.45 weight % C, 0.15~0.25 weight % Si, 1~2.8 weight % Mn, 0.1~0.4 weight % Cr, 0.03~0.1 weight % Zr, 0.01~0.08 weight % Ti, 0.01~0.06 weight % Nb, 0.01~0.1 weight % Co, and the balance is Fe and unavoidable impurity elements.

[0010] A second aspect of the present disclosure provides a method for preparing a laser-welded structural part, the method comprising: using the welding wire described in the first aspect of the present disclosure to laser weld two coated steel plates through a laser wire-filling welding process to obtain a welded steel plate.

[0011] Optionally, the coated steel plate is an Al-Si coated steel plate, and the tensile strength of the Al-Si coated steel plate is not less than 2000 MPa.

[0012] Optionally, the Al-Si coated steel plate comprises a substrate and a coating disposed on a surface of the substrate;

[0013] Optionally, based on the total weight of the substrate, the substrate contains 0.27-0.39 wt% of C, 0.1-0.6 wt% of Si, 0.7-2.2 wt% of Mn, 0.1-0.4 wt% of Al, no more than 0.1 wt% of P, no more than 0.1 wt% of S, no more than 0.7 wt% of Cr, no more than 0.01 wt% of B, no more than 0.16 wt% of Ti, no more than 0.1 wt% of Nb, no more than 0.3 wt% of V, and the balance is Fe and unavoidable impurity elements; and / or,

[0014] Based on the total weight of the coating, the coating contains 80 to 95 wt % of Al, 5 to 11 wt % of Si, and the remainder is Fe and inevitable impurity elements.

[0015] Optionally, the coating has a thickness of 6 to 19 μm, and / or the substrate has a thickness of 1 to 2.5 mm.

[0016] Optionally, the conditions for laser welding include: a butt gap of 0-0.5 mm, a welding speed of 80-120 mm / s, a welding wire diameter of 0.8-1.2 mm, and a wire feeding speed of 80-110 mm / s.

[0017] Optionally, the method further comprises: hot stamping the tailor-welded steel plate to obtain a laser-welded structural part;

[0018] Optionally, the hot stamping forming conditions include: a heating temperature of 880-930°C, a heating time of 200-480s, a quenching cooling rate of 30-50°C / s, and a quenching cooling time of 15-40s.

[0019] In a third aspect of the present disclosure, there is provided a laser welded structural part prepared by the method described in the second aspect of the present disclosure;

[0020] Optionally, the yield strength of the laser-welded structural component is not less than 1200 MPa, the tensile strength is not less than 1700 MPa, the elongation after fracture is not less than 4.5%, and the weld hardness is not less than 520 Hv.

[0021] A fourth aspect of the present disclosure provides a vehicle, comprising the laser-welded structural component described in the third aspect of the present disclosure.

[0022] Through the above technical scheme, the welding wire provided by the present invention can realize high-quality laser welding of high-strength grade steel. The weld has high strength, good toughness, strong resistance to hydrogen-induced delayed cracking, strong versatility and low cost, and is suitable for the production of high-strength, high-safety and lightweight vehicle structural parts and other key industrial components.

[0023] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:

[0025] Figure 1 The metallographic diagram of the laser-welded structural component of Example 9 of the present disclosure is shown;

[0026] Figure 2 A photo of a tensile fracture test of a laser-welded structural component of Example 9 of the present disclosure is shown;

[0027] Figure 3 The hardness distribution diagram of the laser-welded structural component of Example 9 of the present disclosure is shown. DETAILED DESCRIPTION

[0028] The specific implementation of the present disclosure is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described herein is only used to illustrate and explain the present disclosure, and is not used to limit the present disclosure.

[0029] A first aspect of the present disclosure provides a welding wire, which contains, based on the total weight of the welding wire, 0.26-0.48 wt% C (carbon), 0.1-0.3 wt% Si (silicon), 0.8-3 wt% Mn (manganese), 0.1-0.4 wt% Cr (chromium), 0.03-0.1 wt% Zr (zirconium), and the remainder is Fe (iron) and unavoidable impurity elements.

[0030] In the welding wire disclosed in the present invention, an appropriate amount of C element is added to improve the strength and hardness of the material; the Mn element is beneficial to expanding the austenite phase region (γ phase region) in the material and forming an infinite solid solution, thereby improving the hardenability of the material; adding an appropriate amount of Cr element is beneficial to lowering the critical transition temperature of the material, improving the hardenability, and promoting the extensive formation of martensite structure during the quenching process; adding an appropriate amount of Zr element can form stable carbides with the C element, effectively inhibiting the coarsening of austenite grains, thereby promoting a finer martensite structure and improving the toughness of the material.

[0031] In a specific embodiment, the welding wire also contains Ti (titanium), Nb (niobium) and Co (cobalt). By adding Nb and Ti elements in combination, the fine precipitates formed by Nb and Ti, namely carbonitrides, can inhibit the recrystallization and growth of austenite grains through pinning, and these fine dispersed second phase precipitates also provide significant precipitation strengthening effects, effectively improving the strength and hardness of the material; adding an appropriate amount of Co element is beneficial to increasing the martensitic transformation start temperature (Ms point) to obtain a self-tempering effect and reduce the brittleness of the material. At the same time, it is also beneficial to infinitely expand the austenite phase region and reduce the adverse effects of the steel plate coating components (such as Al elements) during the welding process. Specifically, based on the total weight of the welding wire, the welding wire can contain 0.01~0.08 weight% of Ti, 0.01~0.06 weight% of Nb and 0.01~0.1 weight% of Co.

[0032] Furthermore, based on the total weight of the welding wire, the total content of Ti and Nb may be 0.02-0.1 wt %, more preferably 0.04-0.1 wt %. The above range is conducive to further improving the strength and hardness of the material.

[0033] Furthermore, in the welding wire, the weight ratio of Zr element to Ti element is not less than 2.5. After a large number of tests, it is found that when the weight ratio of Zr element to Ti element meets the above conditions, the carbides formed are finer and more dispersed, and have a better toughness improvement effect.

[0034] In a preferred embodiment of the present disclosure, based on the total weight of the welding wire, the welding wire contains 0.3-0.45 wt% C, 0.15-0.25 wt% Si, 1-2.8 wt% Mn, 0.1-0.4 wt% Cr, 0.03-0.1 wt% Zr, 0.01-0.08 wt% Ti, 0.01-0.06 wt% Nb, 0.01-0.1 wt% Co, and the remainder is Fe and unavoidable impurity elements. The above ratio is conducive to further improving the strength, hardness and toughness of the material.

[0035] The welding wire disclosed in the present invention has excellent strength, hardness and toughness, and can be prepared in the form of welding wire, welding plate, welding powder, etc. It has strong versatility and low cost, and can achieve high-quality laser welding of high-strength steel (such as 2000MPa level, 2200MPa level, etc.), and effectively inhibit the diffusion and aggregation of hydrogen in the weld, thereby reducing the probability of crack formation. It is suitable for the production of high-strength, high-safety and lightweight vehicle structural parts and other key industrial components, ensuring the long-term stability and reliability of the structural parts to meet the needs of industrial development.

[0036] The second aspect of the present disclosure provides a method for preparing a laser-welded structural part, which comprises: using the welding wire described in the first aspect of the present disclosure to laser-weld two coated steel plates through a laser wire-filling welding process to obtain a welded steel plate.

[0037] In a specific embodiment, the coated steel plate is an Al-Si coated steel plate, especially a high-strength Al-Si coated steel plate. Specifically, the tensile strength of the Al-Si coated steel plate is not less than 2000MPa. The disclosed method is applicable to two coated steel plates of various strength and thickness combinations, for example, combinations of equal strength, unequal strength, equal thickness, unequal thickness, etc., all of which can achieve good welding quality. For example, the two coated steel plates may include a first Al-Si coated steel plate with a tensile strength of 2000MPa and a second Al-Si coated steel plate with a tensile strength of 2200MPa.

[0038] Furthermore, the Al-Si coated steel plate may include a substrate and a coating disposed on a surface of the substrate.

[0039] In one embodiment, based on the total weight of the substrate, the substrate may contain 0.27-0.39 wt% C, 0.1-0.6 wt% Si, 0.7-2.2 wt% Mn, 0.1-0.4 wt% Al, no more than 0.1 wt% P, no more than 0.1 wt% S, no more than 0.7 wt% Cr, no more than 0.01 wt% B, no more than 0.16 wt% Ti, no more than 0.1 wt% Nb, no more than 0.3 wt% V, and the remainder is Fe and unavoidable impurity elements.

[0040] The thickness of the substrate can be adjusted within a certain range, for example, 1 to 2.5 mm.

[0041] The coating contains Al (aluminum) and Si (silicon). Specifically, based on the total weight of the coating, the coating may contain 80 to 95 weight % of Al, 5 to 11 weight % of Si, and the remainder is Fe and unavoidable impurity elements.

[0042] The thickness of the coating can be adjusted within a certain range, for example, 6 to 19 μm.

[0043] The operating conditions of the laser welding can be adjusted within a wide range, and the welding wire provided by the present disclosure can be particularly well adapted to a wide range of changes in the butt gap of steel plates. Specifically, the conditions of the laser welding may include: a butt gap of 0 to 0.5 mm, a welding speed of 80 to 120 mm / s, a welding wire diameter of 0.8 to 1.2 mm, and a wire feeding speed of 80 to 110 mm / s.

[0044] Furthermore, the method may also include: hot stamping the laser welded material. The hot stamping conditions may include: heating temperature of 880-930°C, heating time of 200-480s, quenching cooling rate of 30-50°C / s, and quenching cooling time of 15-40s.

[0045] In a third aspect of the present disclosure, a laser-welded structural component is provided which is prepared by the method described in the second aspect of the present disclosure.

[0046] The laser-welded structural component disclosed in the present invention has excellent strength, hardness and toughness. Specifically, the yield strength of the laser-welded structural component can be no less than 1200 MPa, preferably no less than 1300 MPa; the tensile strength can be no less than 1700 MPa, preferably no less than 1900 MPa; the elongation after fracture can be no less than 4.5%, preferably no less than 5%; the weld hardness can be no less than 520 Hv, preferably no less than 560 Hv.

[0047] The laser-welded structural component includes a steel plate area and a welding area, the welding area is formed by the welding wire, and the microstructure of the welding area is all martensite. Such a microstructure gives the welding area extremely high hardness and strength, thereby ensuring the reliability of the laser-welded structural component in high-strength applications. In addition, in the tensile test, the fracture position of the laser-welded structural component occurs in the steel plate area (i.e., the parent material area) rather than the welding area. This result shows that the strength of the welding area is higher than that of the steel plate area, and the entire laser-welded structural component exhibits excellent mechanical properties and stability in practical applications.

[0048] A fourth aspect of the present disclosure provides a vehicle, comprising the laser-welded structural component described in the third aspect of the present disclosure.

[0049] In a specific embodiment, the vehicle includes a door ring, and the door ring is made of the laser-welded structural member. The specific structure of the door ring may be common in the art, for example, it may include an A-pillar, a B-pillar, a door sill, an A-pillar upper side beam, a B-pillar upper side beam and other connecting parts. The door ring is made of the laser-welded structural member disclosed in the present invention. As an important part of the vehicle body, it can play a key role in protecting the safety of the driver and passengers in the vehicle when a collision occurs, especially a small offset collision and a side collision, and significantly improve the safety performance of the vehicle.

[0050] The present disclosure is further described in detail below through examples.

[0051] Example 1

[0052] The welding wire of this embodiment has a chemical composition of 0.33 wt% C, 0.21 wt% Si, 1.58 wt% Mn, 0.02 wt% Ti, 0.031 wt% Nb, 0.22 wt% Cr, 0.06 wt% Zr, 0.03 wt% Co, and the remainder is Fe and unavoidable impurity elements.

[0053] Example 2

[0054] The welding wire of this embodiment has a chemical composition of 0.33 wt% C, 0.21 wt% Si, 1.58 wt% Mn, 0.03 wt% Ti, 0.013 wt% Nb, 0.22 wt% Cr, 0.06 wt% Zr, 0.03 wt% Co, and the remainder is Fe and unavoidable impurity elements.

[0055] Example 3

[0056] The welding wire of this embodiment has a chemical composition of 0.33 wt% C, 0.21 wt% Si, 1.58 wt% Mn, 0.01 wt% Ti, 0.02 wt% Nb, 0.22 wt% Cr, 0.06 wt% Zr, 0.03 wt% Co, and the remainder is Fe and unavoidable impurity elements.

[0057] Example 4

[0058] The welding wire of this embodiment has a chemical composition of 0.27 wt% C, 0.21 wt% Si, 1.58 wt% Mn, 0.02 wt% Ti, 0.031 wt% Nb, 0.22 wt% Cr, 0.06 wt% Zr, 0.03 wt% Co, and the remainder is Fe and unavoidable impurity elements.

[0059] Example 5

[0060] The welding wire of this embodiment has a chemical composition of 0.33 wt% C, 0.11 wt% Si, 1.58 wt% Mn, 0.02 wt% Ti, 0.031 wt% Nb, 0.22 wt% Cr, 0.06 wt% Zr, 0.03 wt% Co, and the remainder is Fe and unavoidable impurity elements.

[0061] Example 6

[0062] The welding wire of this embodiment has a chemical composition of 0.33 wt% C, 0.21 wt% Si, 1.58 wt% Mn, 0.02 wt% Ti, 0.031 wt% Nb, 0.22 wt% Cr, 0.06 wt% Zr, and the remainder is Fe and unavoidable impurity elements.

[0063] Example 7

[0064] The welding wire of this embodiment has a chemical composition of 0.33 wt% C, 0.21 wt% Si, 0.8 wt% Mn, 0.02 wt% Ti, 0.031 wt% Nb, 0.22 wt% Cr, 0.06 wt% Zr, 0.03 wt% Co, and the remainder is Fe and unavoidable impurity elements.

[0065] Example 8

[0066] The welding wire of this embodiment has a chemical composition of 0.33 wt% C, 0.21 wt% Si, 1.58 wt% Mn, 0.22 wt% Cr, 0.06 wt% Zr, 0.03 wt% Co, and the remainder is Fe and unavoidable impurity elements.

[0067] Comparative Example 1

[0068] The welding wire of this comparative example has a chemical composition of 0.22 wt% C, 0.21 wt% Si, 1.58 wt% Mn, 0.03 wt% Ti, 0.031 wt% Nb, 0.22 wt% Cr, 0.06 wt% Zr, 0.03 wt% Co, and the remainder is Fe and inevitable impurity elements.

[0069] Comparative Example 2

[0070] The welding wire of this comparative example has a chemical composition of 0.33 wt% C, 0.21 wt% Si, 0.61 wt% Mn, 0.03 wt% Ti, 0.031 wt% Nb, 0.22 wt% Cr, 0.06 wt% Zr, 0.03 wt% Co, and the remainder is Fe and inevitable impurity elements.

[0071] Comparative Example 3

[0072] The welding wire of this comparative example has a chemical composition of 0.33 wt% C, 0.21 wt% Si, 1.58 wt% Mn, 0.03 wt% Ti, 0.031 wt% Nb, 0.22 wt% Cr, 0.02 wt% Zr, 0.03 wt% Co, and the remainder is Fe and inevitable impurity elements.

[0073] Comparative Example 4

[0074] The welding wire of this comparative example has a chemical composition of 0.33 wt% C, 0.44 wt% Si, 1.58 wt% Mn, 0.03 wt% Ti, 0.031 wt% Nb, 0.22 wt% Cr, 0.06 wt% Zr, 0.03 wt% Co, and the remainder is Fe and inevitable impurity elements.

[0075] Comparative Example 5

[0076] The welding wire of this comparative example has a chemical composition of 0.22 wt% C, 0.25 wt% Si, 1.24 wt% Mn, 0.03 wt% Ti, 0.17 wt% Cr, 0.045 wt% Al, and the remainder is Fe and inevitable impurity elements.

[0077] Comparative Example 6

[0078] The welding wire of this comparative example has a chemical composition of 0.24 wt% C, 0.01 wt% Si, 1.43 wt% Mn, 0.02 wt% Ti, 0.012 wt% Nb, 0.23 wt% Cr, 0.003 wt% N, 6.7 wt% Ni, 0.035 wt% Al, and the remainder is Fe and unavoidable impurity elements.

[0079] Comparative Example 7

[0080] The welding wire of this comparative example has a chemical composition of 0.04 wt% C, 0.25 wt% Si, 1.54 wt% Mn, 0.17 wt% W, 0.05 wt% Nb, 0.2 wt% Cr, 0.8 wt% Mo, 4.05 wt% Ni, 0.14 wt% Cu, and the remainder is Fe and inevitable impurity elements.

[0081] Comparative Example 8

[0082] The welding wire of this comparative example has a chemical composition of 0.2 wt% C, 0.35 wt% Si, 2.31 wt% Mn, 0.025 wt% Nb, 2.24 wt% Cr, 4.11 wt% Ni, and the remainder is Fe and inevitable impurity elements.

[0083] Table 1 shows the compositions (unit: weight %) of the welding wires of Examples 1 to 8 and Comparative Examples 1 to 8.

[0084] Table 1

[0085]

[0086] Embodiments 9 to 16

[0087] The welding wire of Examples 1 to 8 is used to prepare laser-welded structural parts, and the specific steps are as follows: two Al-Si coated steel plates are laser welded under the following conditions: the steel plate butt gap is 0.3 mm, the welding speed is 100 mm / s, the welding wire diameter is 1.0 mm, and the wire feeding speed is 100 mm / s to obtain a welded steel plate, and then heated in a 900°C roller hearth furnace for 380 seconds, quenched at a cooling rate of 40°C / s, the quenching cooling time is 20 seconds, and cooled in a mold to below 300°C to obtain a laser-welded structural part.

[0088] In the Al-Si coated steel sheet, the substrate composition (excluding Fe and inevitable impurity elements), thickness and tensile strength are listed in Table 2 (unit, weight %), the coating composition is: 88 weight % Al, 9 weight % Si, the balance is Fe and inevitable impurity element components, and the coating thickness is 10 μm.

[0089] Comparative Examples 9-16

[0090] The welding wires of Comparative Examples 1 to 8 were used to prepare laser-welded structural parts according to the method of Example 9.

[0091] Table 2

[0092]

[0093] Test Example 1

[0094] The weld metallographic inspection and performance inspection were performed on the laser-welded structural parts prepared in Examples 9 to 16 and Comparative Examples 9 to 16. The specific results are shown in Table 3.

[0095] The metallographic detection method is: GB / T 13298 Metal Microstructure Inspection Method. The metallographic image of the welding area of ​​the laser welded structural component of Example 9 is as follows: Figure 1 As shown, it can be seen that the microstructure of the welding zone (i.e., the weld) is all martensite; the metallographic images of the welding zone of the laser welded structural parts of Examples 10 to 16 are Figure 1 similar.

[0096] The test method for tensile fracture mechanical properties is: GB / T 228.1 Tensile test of metallic materials Part 1: Room temperature test method. The tensile fracture test results of the laser welded structural parts of Example 9 are as follows: Figure 2 As shown, it can be seen that the fracture position occurs in the steel plate area (i.e., the parent material area) on the left side of the welding area (i.e., the weld); the tensile fracture test photos of the laser welded structural parts of Examples 10 to 16 and Figure 2 similar.

[0097] The hardness test method is: GB / T 4340.1 Metallic materials Vickers hardness test Part 1: Test method. The hardness distribution test results of the laser welded structural parts of Example 1 are as follows: Figure 3 As shown, the hardness distribution of the welding area (i.e., weld) is 574~598 Hv, and the hardness distribution of the low-strength steel plate area (i.e., parent material area) is 563~569 Hv.

[0098] Table 3

[0099]

[0100] In Table 3, F represents the weld microstructure type of ferrite, and M represents the weld microstructure type of martensite.

[0101] It can be seen from Table 3 that the laser-welded structural parts prepared by using the welding wire disclosed in the present invention exhibit higher tensile strength, yield strength, elongation after fracture and minimum hardness of the weld.

[0102] Test Example 2

[0103] The laser welded structural parts prepared in Example 1 and Comparative Example 1 were subjected to hydrogen-induced delayed cracking tests, and the test method was: GB / T 40403-2021 Corrosion of metals and alloys - Method for determining the stress corrosion cracking resistance of metals by four-point bending method, the stress level of the samples was selected as 100% yield strength, and the samples were stored in an air medium at 15-30°C. The specific results are shown in Table 4.

[0104] Table 4

[0105]

[0106] It can be seen from Table 4 that the laser welded structural parts prepared by using the welding wire disclosed in the present invention show more excellent hydrogen-induced delayed cracking performance.

[0107] The preferred embodiments of the present disclosure are described in detail above in conjunction with the accompanying drawings; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.

[0108] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.

[0109] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.

Claims

1. A welding wire, It is characterized in that Based on the total weight of the welding wire, the welding wire contains 0.26-0.48 wt% of C, 0.1-0.3 wt% of Si, 0.8-3 wt% of Mn, 0.1-0.4 wt% of Cr, 0.03-0.1 wt% of Zr, 0.01-0.08 wt% of Ti, 0.01-0.06 wt% of Nb and 0.01-0.1 wt% of Co, and the balance is Fe and unavoidable impurity elements; wherein, based on the total weight of the welding wire, the total content of Ti element and Nb element is 0.02-0.1 wt%.

2. The welding wire according to claim 1, in, In the welding wire, the weight ratio of Zr element to Ti element is not less than 2.

5.

3. The welding wire according to claim 1 or 2, in, Based on the total weight of the welding wire, the welding wire contains 0.3-0.45 wt% of C, 0.15-0.25 wt% of Si, 1-2.8 wt% of Mn, 0.1-0.4 wt% of Cr, 0.03-0.1 wt% of Zr, 0.01-0.08 wt% of Ti, 0.01-0.06 wt% of Nb, 0.01-0.1 wt% of Co, and the balance is Fe and inevitable impurity elements.

4. A method for preparing a laser welded structural part, It is characterized in that The method comprises: using the welding wire described in any one of claims 1 to 3 to laser weld two coated steel plates through a laser wire-filling welding process to obtain welded steel plates.

5. The method according to claim 4, in, The coated steel plate is an Al-Si coated steel plate, and the tensile strength of the Al-Si coated steel plate is not less than 2000 MPa.

6. The method according to claim 5, in, The Al-Si coated steel plate comprises a substrate and a coating disposed on the surface of the substrate.

7. The method according to claim 6, in, Based on the total weight of the substrate, the substrate contains 0.27-0.39 wt% of C, 0.1-0.6 wt% of Si, 0.7-2.2 wt% of Mn, 0.1-0.4 wt% of Al, not more than 0.1 wt% of P, not more than 0.1 wt% of S, not more than 0.7 wt% of Cr, not more than 0.01 wt% of B, not more than 0.16 wt% of Ti, not more than 0.1 wt% of Nb, not more than 0.3 wt% of V, and the balance is Fe and unavoidable impurity elements; and / or, Based on the total weight of the coating, the coating contains 80 to 95 wt % of Al, 5 to 11 wt % of Si, and the remainder is Fe and inevitable impurity elements.

8. The method according to claim 6, in, The thickness of the coating is 6-19 μm, and / or the thickness of the substrate is 1-2.5 mm.

9. The method according to claim 4, in, The conditions for laser welding include: a butt gap of 0-0.5 mm, a welding speed of 80-120 mm / s, a welding wire diameter of 0.8-1.2 mm, and a wire feeding speed of 80-110 mm / s.

10. The method according to claim 4, in, The method further comprises: hot stamping the tailor-welded steel plate to obtain a laser-welded structural part.

11. The method according to claim 10, in, The hot stamping forming conditions include: heating temperature of 880-930°C, heating time of 200-480s, quenching cooling rate of 30-50°C / s, and quenching cooling time of 15-40s.

12. A laser welded structural part prepared by the method according to any one of claims 4 to 11.

13. The laser welded structural component according to claim 12, in, The yield strength of the laser welded structural component is not less than 1200 MPa, the tensile strength is not less than 1700 MPa, the elongation after fracture is not less than 4.5%, and the weld hardness is not less than 520 Hv.

14. A vehicle, It is characterized in that Including the laser welded structural part according to claim 12 or 13.

Citation Information

Patent Citations

  • Repair-welding material for die

    CN109773368A

  • Manufacturing method for hydrogen induced cracking resistant laser welding joint of aluminum-silicon coating hot forming steel

    CN116493756A